A DNA nanopillar as a scaffold to regulate the ratio and distance of mimic enzymes for an efficient cascade catalytic platform. Issue 1 (6th November 2020) - Kou, Bei-Bei; Chai, Ya-Qin; Yuan, Ya-Li; Yuan, Ruo
Abstract : A rigid 3D DNA nanopillar was used to investigate the influence of spatial organization on the cascade activity in multienzyme systems, realizing controllable regulation of the mimic enzyme ratio and spacing for efficient cascade catalytic platform. Abstract : Herein, a rigid 3D DNA nanopillar was used to investigate the influence of spatial organization on the cascade activity in multienzyme systems, realizing controllable regulation of the mimic enzyme ratio and spacing for acquiring a high-efficiency enzyme cascade catalytic platform. Initially, the ratio of mimic enzyme AuNPs (glucose oxidase-like activity) and hemin/G-quadruplex DNAzyme (peroxidase-like activity) fixed at the designed position was adjusted by changing the number of edges in a DNA polyhedron, resulting in an optimal mimic enzyme ratio of 1 : 4 with a quadrangular prism as the scaffold. Notably, the DNA nanopillar formed by quadrangular prism layer-by-layer assembly acted as a track for directional and controllable movement of a bipedal DNA walker based on the toehold mediated strand displacement reaction (TSDR), which endowed the assay system with continuous enzyme spacing regulation compared with previous enzyme cascade systems that induced inflexible operation. Furthermore, enzyme mimetics in this work circumvented the drawbacks of natural enzymes, such as time-consuming purification processes and poor thermal stability. As a proof of concept, the proposed dual regulation strategy of cascade enzymes was applied in the ultrasensitive electrochemical detection of Pb 2+, which provided a new route to fabrication of high-performance artificial enzyme cascade platforms for ultimate application in bioanalysis and biodiagnostics.